EFFECTS OF IN VIVO GENE TRANSDUCTION OF ANTI－MDR1 RIBOZYME IN COMBINATION WITH CHEMOTHERAPY ON MULTIDRUG－RESISTANT HUMAN LYMPHOMA GROWTH IN MICE - 徐东平 王福生 OhnumaTakao 金磊 (Chinese journal of cancer research, 2003)
Objective: To study the effect of adenovlrus- mediated transfer of anti-MDRl ribozyme on the reversal of multidrug resistant (MDR) phenotype of P-glycoprotein(P-gp)-positive Daudi human Burkitt lymphoma both in vitro and in viro. Methods: A recombinant adenovirus expressing 196Rz (Adv-196Rz) was developed and functionally evaluated. SCID mice inoculated subcutaneously (s.c.) with 5×10^6 Daudi/MDR20 cells were locally treated with Adv-196Rz or mock virus (Adv-Mock)at the multiplicity of infection (MOI) of 400 PFU once a day for 3 consecutive days. Then the mice were intraperitoneally (i.p.) administrated with vincristine (VCR)450ng/g for 5 consecutive days. Results: In vitro employment of Adv-196Rz was able to interrupt MDR1 transcription, to inhibit P-gp expression and to restore drug sensitivity to VCR of Daudi/MDR20 cells. In vivo, 87.5 % (7/8)of Daudi/MDR20-inoculated mice treated with Adv-Mock+VCR developed palpable tumor by the 6th week and died or were sacrificed (because of tumor weight > 10% of body weight) by the llth week. In contrast, among 9 Daudi/MDR20-inoculated mice treated with Adv-196Rz +VCR, only 3 developed tumor by the 11th, 13th and 14th week, respectively. 66.7% of mice survived >120 days in tumor-free. The survival difference between the two groups was very significant (P<0.01). Conclusion: Adenovirus-mediated Transfer of 196Rz can revert drug resistance of MDR tumor cells both in vitro and in vivo. Adv-196Rz may prove useful as an adjuvant in the chemotherapy of P-gp mediated MDR human tumors.